An Analysis the Rupiah Exchange Rates Effect Against the American Dollar and Inflation Against the Growth of Islamic Banking Mudharabah Deposits in Indonesia - Tho'in, Muhammad; Prastiwi, Iin Emy (International Journal of Islamic Business and Economics (IJIBEC), 2019)
This study aims to determine the effect of rupiah exchange rate on the US dollar (US dollar) and inflation on Mudharabah deposits of Islamic banking in Indonesia. This research is a descriptive quantitative study with secondary data. This study took samples at Islamic Commercial Banks and Islamic Business Units from January 2013 to December 2017. The analysis technique used was multiple linear regression analysis. Before conducting regression testing, the data were tested by classical assumption test, namely normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The results in this study are the first rupiah exchange rate has a significant effect on Mudharabah deposits in a positive direction. This means that if rupiah exchange rate increases the impact on community activities in investing in Mudharabah deposits increases. The second is that iinflation has no significant effect on Mudharabah deposits, but has a relationship with a positive direction. This means that if the inflation increases, the impact on community activities in investing Mudharabah deposits also increases. Third, rupiah exchange rate and inflations are simultaneously affect on the Mudharabah deposits of Islamic banking in the amount of 59.9%. The implication is that the high rupiah exchange rate situation attracts investors to invest in Mudharabah deposits. The increase in the rupiah against the US dollar tends to cause multiplier effect which results in rising prices of commodity goods. High prices of commodity goods cause macro consumption to decrease, too because people tend to be efficient in consumption.